1996
DOI: 10.1111/j.1432-1033.1996.0221t.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited Proteolysis of β‐Conglycinin and Glycinin, the 7S and 11S Storage Globulins from Soybean [Glycine Max (L.) Merr.]

Abstract: The G2 (A2BIa) glycinin subunit from soybean (Clycine mux L. Merr.) was purified and renatured to the homohexameric holoprotein. This protein along with purified P-conglycinin were subjected to limited proteolysis by trypsin. The generated polypeptide fragments were separated via SDS/PAGE and the amino acid sequence of the N-terminals was determined. Four cleavage points were detected in the a-chain A2 of glycinin as well as in the a'-chain of P-conglycinin. From the known three-dimensional structure of 7 s gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…Interestingly, this G2a epitope was part of a corresponding region of a G1a epitope identified by our group in an earlier study [17] and was also adjacent to an Ara h 3 epitope (G240-A254) identified by Rabjohn et al [16]. Structurally, this potentially allergenic epitope is located in a domain between two variable regions of legume glycinins, which have been identified as residing on the surface of the protein and susceptible to protease cleavage [12,23]. In the tertiary structure of the glycinin trimer, this domain corresponds to the subunit interface region ( Figure 6A).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, this G2a epitope was part of a corresponding region of a G1a epitope identified by our group in an earlier study [17] and was also adjacent to an Ara h 3 epitope (G240-A254) identified by Rabjohn et al [16]. Structurally, this potentially allergenic epitope is located in a domain between two variable regions of legume glycinins, which have been identified as residing on the surface of the protein and susceptible to protease cleavage [12,23]. In the tertiary structure of the glycinin trimer, this domain corresponds to the subunit interface region ( Figure 6A).…”
Section: Discussionmentioning
confidence: 98%
“…This linker region seems to be a hypervariable site among legume seed storage proteins and contains specific sites for proteolytic cleavage in vivo. For example, the soybean glycinins are proteolytically processed in vivo in the linker region joining the cupin domains to form the acidic and basic chains of the mature proteins (Shutov et al 1995(Shutov et al , 1996(Shutov et al , 1998(Shutov et al , 1999. Therefore, these regions of plant cupin allergens could be points of attack in the mammalian digestive tract, yielding potentially allergenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Both epitope A and epitope B reside in a domain between two variable regions (variable region 2, residues Q188–E216, and the hypervariable region, residues T269–K306 [24]) that may represent a particularly allergenic domain of legume seed storage proteins. This glycinin acidic chain domain, between variable region 2 and the hypervariable region [24], corresponds to α-helices α1, α2, α3 and β-strand J′ of the proposed model of 11S legumin protein structure [29, 30]. This domain is located at the subunit interface of the 7S trimer that corresponds to half of the 11S hexamer [30].…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of glycinin, in comparison with similar legume family proteins, possesses three variable regions [24]. These regions have been identified as residing at the surface of the glycinin subunit since proteolytic cleavage occurs at or near these variable regions [24, 29]. Both epitope A and epitope B reside in a domain between two variable regions (variable region 2, residues Q188–E216, and the hypervariable region, residues T269–K306 [24]) that may represent a particularly allergenic domain of legume seed storage proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation